Consumer selection and home health agency quality and patient experience stars. (18th October 2021) - Schwartz, Margot L.; Rahman, Momotazur; Thomas, Kali S.; Konetzka, R. Tamara; Mor, Vincent
Abstract: Objective: To compare the impact of the introduction of two distinct sets of star ratings, quality of care, and patient experience, on home health agency (HHA) selection. Data Sources: We utilized 2014–2016 home health Outcome and Assessment Information Set (OASIS) assessments, as well as publicly reported data from the Home Health Compare website. Data Collection/Extraction Methods: We identified a 5% random sample of admissions (186, 498 admissions) for new Medicare Fee‐for‐Service home health users. Study Design: This admission‐level assessment compared HHA selection before (July 2014–June 2015) and after (February–December 2016) star ratings were published. We utilized a conditional logit, discrete choice model, which accounted for all HHAs that each patient could have selected (i.e., the choice set) based on ZIP codes. Our explanatory variables of interest were the interactions between star ratings and time period (pre/post stars). We stratified our analyses by race, admission source, and Medicaid eligibility. We adjusted for HHA characteristics and distance between patients' homes and HHAs. Principal Findings: The introduction of star ratings was associated with a 0.88‐percentage‐point increase in the probability of selecting a high‐quality HHA and a 0.81‐percentage‐point increase in the probability of selecting a highly ranked patient experience HHA. Patients admitted from the community, and black and Medicare–Medicaid dual‐eligible beneficiaries experienced larger increases in their likelihood of selecting high‐rated agencies than inpatient, white, and nondual beneficiaries. Conclusions: The introduction of quality of care and patient experience stars were associated with changes in HHA selection; however, the strength of these relationships was weaker than observed in other health care settings where a single star rating was reported. The introduction of star ratings may mitigate disparities in HHA selection. Our findings highlight the importance of reporting information about quality and satisfaction separately and conducting research to understand the mechanisms driving HHA selection.